Analysis Study of “Food Cholesterol Detect” Application Development in Early Detection of High Cholesterol Food Consumption - Terati, Terati; Nazarena, Yunita; Sadiq, Ahmad (Poltekkes Kemenkes Jakarta III, 2023)
The incidence of hypercholesterolemia in Indonesia is increasing daily, caused by a sinful lifestyle, lack of physical activity, and high consumption of foods high in fat. Patients with hypercholesterolemia have a cholesterol intake from food consumed by 46%. Related to these problems, we need a technology that can make it easier for people to manage the consumption of foods high in cholesterol by utilizing the sophistication of Smartphones. So researchers are interested in designing an application,